Encoding Multilayer Complexity in Anti‐Counterfeiting Heterometallic MOF‐Based Optical Tags. Issue 3 (14th December 2020) - Deneff, Jacob I.; Butler, Kimberly S.; Rohwer, Lauren E. S.; Pearce, Charles J.; Valdez, Nichole R.; Rodriguez, Mark A.; Luk, Ting S.; Sava Gallis, Dorina F.
Abstract: Optical tags provide a way to quickly and unambiguously identify valuable assets. Current tag fluorophore options lack the tunability to allow combined methods of encoding in a single material. Herein we report a design strategy to encode multilayer complexity in a family of heterometallic rare‐earth metal–organic frameworks based on highly connected nonanuclear clusters. To impart both intricacy and security, a synergistic approach was implemented resulting in both overt (visible) and covert (near‐infrared, NIR) properties, with concomitant multi‐emissive spectra and tunable luminescence lifetimes. Tag authentication is validated with a variety of orthogonal detection methodologies. Importantly, the effect induced by subtle compositional changes on intermetallic energy transfer, and thus on the resulting photophysical properties, is demonstrated. This strategy can be widely implemented to create a large library of highly complex, difficult‐to‐counterfeit optical tags. Abstract : To increase complexity and security in optical tags, heterometallic rare‐earth metal–organic frameworks with both overt (visible) and covert (near‐infrared) properties were targeted. Multilayer intricacy is imparted by concomitant multi‐emissive spectra and highly tunable luminescence lifetimes. Intermetal charge transfer in these systems results in difficult‐to‐counterfeit optical tags with unique photophysical properties.